2022
DOI: 10.21873/invivo.12811
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Systemic or Intraperitoneal Administration of Anti-PD-1 Antibody for Peritoneal Metastases from Gastric Cancer

Abstract: Background/Aim: Programmed death-1 (PD-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Optimal treatment schedules are lacking and are hampered by the heterogeneity of evidence. Intraperitoneal immunotherapy, such as checkpoint inhibitors or tumor-specific antibodies, might be a promising route for in the future, but current evidence is confined to animal-studies only [62,63]. To generalize the use of intraperitoneal chemotherapy and to determine the optimal drug combination, studies directly comparing different regimens are warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimal treatment schedules are lacking and are hampered by the heterogeneity of evidence. Intraperitoneal immunotherapy, such as checkpoint inhibitors or tumor-specific antibodies, might be a promising route for in the future, but current evidence is confined to animal-studies only [62,63]. To generalize the use of intraperitoneal chemotherapy and to determine the optimal drug combination, studies directly comparing different regimens are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…These novel methods might enhance intraperitoneal drug delivery by prolonging its local exposure, but no clinical or pharmacokinetic studies in patients with unresectable peritoneal disease have been performed so far. Intraperitoneal immunotherapy (anti-PD-1 therapy) has been studied in vivo for intraperitoneal use [62,63]. A cellular immune response has been shown in mouse models and might therefore have potential as an intraperitoneal drug, but as yet, no pharmacokinetic or clinical data are available demonstrating this rationale.…”
Section: Novel Intraperitoneal Agentsmentioning
confidence: 99%
“…This particular cell line was generously provided by Dr. S. Nomura from Tokyo University, Japan. A highly metastatic subline YTN16P was established through an in vivo selection method involving repeated intraperitoneal administration of the metastatic subline of YTN16 34 . Culturing of these cells was conducted in Dulbecco’s Modified Eagle Medium (DMEM) supplemented with 10% fetal bovine serum (FBS; Sigma, St. Louis, MO, USA), 50U/mL penicillin, 50 mg/mL streptomycin (Life Technologies, Grand Island, NY, USA), 2.5 µg/mL Plasmocin prophylactic (InvivoGen, San Diego, USA), and an additional 2 µM/mL L-Glutamine (G7513 200 mM; Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…In research utilizing a newly produced highly metastatic clone of murine gastric cancer cells, YTN16P, it was shown that infusion of PD-1 mAb through the intravenous or intraperitoneal route lowered the rate of metastasis development on the mesenteric surface by 30–40% as a monotherapy [ 46 ]. Additionally, previous studies utilizing colon [ 40 , 47 ] or ovarian cancer cells [ 48 , 49 , 50 ] have shown that anti-PD-1 mAb may partially, but not fully, inhibit the development of PM in immunocompetent animals.…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%